Worthy or not worthy? Repair motivations and barriers from consumers across fashion, furniture, and consumer electronics in Denmark - Hansen, Andreas Kornmaaler; Laursen, Linda Nhu; Jørgensen, Michael Søgaard; Markussen, Tanja (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Never has human consumption and demand for products been this high, and the growing demand for products puts a strain on the finite resources available. Therefore, the need for prolonging the lifetime of existing consumer products has received increasing attention from governing bodies such as the European Commission e.g. shown in the ‘right-to-repair’ directive. While 77% percent of European citizens state they want to repair products before buying new, only 64% state that they have done it – and 90% have never purchased clothing, smartphones, or televisions secondhand. Prolonging the lifetime of consumer products through repair is therefore an important point towards more sustainable consumption. Yet, a lot of broken products never enter a repair process. This paper aims to shed light on the barriers and motivations for repair to help increase the understanding of how more repairable products can get repaired. Through a Danish national survey (N=1068) and 11 semi-structured interviews, we identify main barriers and motivations for entering a repair process within three main product classifications: Consumer electronics, Fashion, and Furniture. We confirm existing findings that price of repair/replacement is a main motivator/barrier. We also identify perceived repairability and ease of cassation or replacement as barriers not previously described.